Biochemical evidence of the expression of two major histocompatibility complex class I genes on bovine peripheral blood mononuclear cells - Joosten, I.; Teale, A.J.; Poel, A. van der; Hensen, E.J. (Wiley, 1992)
Summary. For a long time, the bovine major histocompatibility complex (MHC) (BOLA) class I region was characterized, rather uniquely among mammalian species, as having one expressed locus. Recent reports have suggested otherwise. Selective immunoprecipitation and molecular characteriztion of products enable a decisive answer to the question of whether there is indeed more than one locus expressed. Therefore, we characterized serologically defined w10 encoding haplotypes in European and African cattle by immunoprecipitation of [35S]‐methioninelabelled peripheral blood mononuclear cells (PBMC), followed by one‐ and two‐dimensional isoelectric focusing (1D/2D‐IEF) of cell lysates. Monoclonal antibodies (mAb) used were directed against either human class I monomorphic determinants (W6/32 and B1.1G6) or bovine polymorphic determinants expressed on products encoded by serologically defined w10 encoding haplotypes of Boran and Friesian cattle. Sequential immunoprecipitations with W6/32 and B1.1G6 using lysates of PBMC of British Friesian cattle, revealed that from this haplotype W6/32 precipitated one product, whereas B1.1G6 precipitated two products. The product precipitated in addition appeared to be the one that was selectively precipitated by the mAb directed against polymorphic determinants on a product of w10 encoding haplotypes. Additionally, peptide maps of protease V8‐digested precipitates showed that this particular ‘w10’ associated product was distinctly different from the product recognized by W6/32. Thus, we suggest that the two products are distinct gene products and that the product with higher PI is associated with the serologically defined A‐locus product, whereas the product with lower PI is the putative second locus product.In the African Boran breed, variants of the serologically defined w10 specificity were found on the basis of IEF typing. These variants appeared to be associated with different second locus products. Therefore, we conclude that serologically defined w10 encoding haplotypes encode at least two independent class I locus products, expressed on normal bovine PBMC. In IEF analysis the additional use of mAb recognizing polymorphic determinants on serologically defined A‐locus products highly facilitated the detection and typing of second locus products.